Understanding the role of corporate social responsibility and sustainable supply chain management in shaping the consumers’ intention to use sharing platforms - Li, Wenjie; Waris, Idrees; Sun, Chaojing; Hameed, Irfan; Bhutto, Muhammad Yaseen; Ali, Rashid (Frontiers in Psychology, 2022)
Sustainable supply chain management (SSCM) in the sharing economy platforms supports resource management and achieves environmental sustainability. Corporate social responsibility (CSR) is an essential pillar of sustainability, but the link between CSR and SSCM has been missing in the literature. Therefore, the current study intends to examine the connection between CSR and SSCM practices in the sharing economy-based platforms. This study has applied the Means to end theory to understand customer intention in the sharing economy. The data of 379 respondents from five main cities of Pakistan has been collected through convenience sampling. Partial Least Square Structural Equation Modeling (PLS-SEM) has been used to test the proposed conceptual model. The study results show that the corporate social responsibility approach adopted by the sharing economy platforms improves internal supply chain management that drives customers' intention to use sharing economy platforms. Green concern has a significant moderating effect on customers' tendency towards environmental issues and solutions. However, findings revealed that eco-design in the sustainable supply chain do not affect customer purchase intention in sharing economy platforms. The study's findings provide practical implications to organizations focusing on sustainable supply chain management practices in the sharing economy.